2021
DOI: 10.30941/cestems.2021.00034
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cogging torque and electromagnetic vibration based on different combination of pole arc coefficient for interior permanent magnet synchronous machine

Abstract: Cogging torque and electromagnetic vibration are two important factors for evaluating permanent magnet synchronous machine (PMSM) and are key issues that must be considered and resolved in the design and manufacture of high-performance PMSM for electric vehicles. A fast and accurate magnetic field calculation model for interior permanent magnet synchronous machine (IPMSM) is proposed in this article.Based on the traditional magnetic potential permeance method, the stator cogging effect and complex boundary con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Some of these techniques involve the optimum design of stator elements, such as, for example, the skewing of the lamination stack [5,6], or the modification of the stator tooth width [7]. The cogging torque can also be minimized by acting on the pole arc width, as described in [8,9]. An interesting alternative to the latest technique is proposed in [10,11], where the cogging torque is reduced by determining not only an adequate width of the polar arc, but also an optimized shape.…”
Section: An Overview Of the Cogging Torque Minimization Techniquesmentioning
confidence: 99%
“…Some of these techniques involve the optimum design of stator elements, such as, for example, the skewing of the lamination stack [5,6], or the modification of the stator tooth width [7]. The cogging torque can also be minimized by acting on the pole arc width, as described in [8,9]. An interesting alternative to the latest technique is proposed in [10,11], where the cogging torque is reduced by determining not only an adequate width of the polar arc, but also an optimized shape.…”
Section: An Overview Of the Cogging Torque Minimization Techniquesmentioning
confidence: 99%
“…According to Equation (1), the groove torque can be reduced by reducing the Nz / 2P sub-Fourier decomposition coefficient Brnz/2p. Groove torque and 6k (k= 1,2,3...) For the built-in permanent magnet motor, the polar arc coefficient can be expressed by the central Angle corresponding to the two arcs.a [6] 2…”
Section: Analytical Expressionmentioning
confidence: 99%
“…Cogging torque is an inherent property of permanent magnet motor, and its size affects the stability of motor operation. Therefore, high-performance motor needs low cogging torque [20]. Previous studies have shown that the application of new soft magnetic materials in the motor can effectively improve the efficiency of the motor.…”
Section: A Optimization Objectives and Optimization Factorsmentioning
confidence: 99%